Pengembangan Sistem Informasi Jurnal Mengajar Guru Berbasis Web Menggunakan Framework CodeIgniter - Setiyana Haridian; Budi Hartono; Arsito Ari Kuncoro (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Manual teaching journal management at SMA Negeri 1 Kayen frequently leads to documentation inefficiencies, risks of data loss, and challenges in the teaching supervision process. This research tends to design and develop a web-based teacher teaching journal information system employing the CodeIgniter 3 framework with a Model-View-Controller (MVC) architecture. The system was improved employing the Waterfall methodology, comprising requirements analysis, system design, implementation, testing, and maintenance phases. The system integrates four user roles—administrator, teacher, student, and supervisor—to support the digitalization of recording processes, real-time teacher attendance verification by students, and centralized activity monitoring. Black Box Testing outcomes present that all system functions, involving authentication, data management, and reporting, operate 100% in accordance with user requirements. The implementation of this system effectively reduces administrative time compared to manual methods while enhancing the accountability and transparency of teaching journal management within the school. With centralized data integration, this system helps as an effective solution for supporting data-driven managerial decision-making in education.